Employing the Linguistic Corpus in Teaching Arabic Writing Skill: A Proposed Instructional Model for the Arabic Program - Ilham Fatkhu Romadhon; Muassomah; Zakiyah Arifa (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study proposes an instructional model for teaching Arabic writing skills to students of the Program for Arabic Language (PKPBA) at Maulana Malik Ibrahim State Islamic University Malang, Indonesia, based on the use of a language corpus. The novelty of this model lies in the integration of three instructional resources (PowerPoint presentations, Sketch Engine corpus analysis software, and worksheets) grounded in a single, locally relevant corpus ('Indonesia Al-Youm'), which has not been systematically employed in previous corpus-based Arabic writing instruction. Using a descriptive-analytical method based on document analysis and expert validation, the study found that the teaching materials received an average score of 4.32 (very appropriate) and the learning design received 2.70 (appropriate), confirming the model's suitability for field implementation from an expert perspective. The model consists of five sequential steps: concept presentation, guided corpus exploration, analytical exercises, guided writing production, and reflection with feedback. As an expert-validated proposal, this model offers a conceptual framework that potentially bridges the gap between declarative knowledge and procedural skills in teaching Modern Standard Arabic writing, though empirical testing with learners remains necessary.